2019
DOI: 10.1002/glia.23691
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila ClC‐a is required in glia of the stem cell niche for proper neurogenesis and wiring of neural circuits

Abstract: Glial cells form part of the neural stem cell niche and express a wide variety of ion channels; however, the contribution of these channels to nervous system development is poorly understood. We explored the function of the Drosophila ClC‐a chloride channel, since its mammalian ortholog CLCN2 is expressed in glial cells, and defective channel function results in leukodystrophies, which in humans are accompanied by cognitive impairment. We found that ClC‐a was expressed in the niche in cortex glia, which are cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 124 publications
1
20
0
Order By: Relevance
“…Next, we analyzed the expression of Slit ligand using a previously described slit:GFP line [ sli MI03825–GFSTF.2 , ( Caipo et al, 2020 ; Plazaola-Sasieta et al, 2019 ; Venken et al, 2011 )]. We found that Slit was expressed in populations of glial cells that surround the p-IPC neuroepithelium and migratory progenitors (see arrowheads and arrow in Supplementary Figures 2G–I′″ ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we analyzed the expression of Slit ligand using a previously described slit:GFP line [ sli MI03825–GFSTF.2 , ( Caipo et al, 2020 ; Plazaola-Sasieta et al, 2019 ; Venken et al, 2011 )]. We found that Slit was expressed in populations of glial cells that surround the p-IPC neuroepithelium and migratory progenitors (see arrowheads and arrow in Supplementary Figures 2G–I′″ ).…”
Section: Resultsmentioning
confidence: 99%
“…CLCN2 encodes chloride channel 2 (CLC-2), which is a type of permeable chloride channel that belongs to the family of CLCN2 channel/transport proteins ( 13 ). CLCN2 is expressed in glia precursors during development and is required for their differentiation into astrocytes and oligodendrocytes ( 14 , 15 ). Mutations in CLCN2 are responsible for leukoencephalopathy with ataxia ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these glial cells control neuroblast proliferation (Coutinho-Budd et al, 2017;Read, 2018;Spéder & Brand, 2018). The effect on neurogenesis requires the chloride channel ClC-a which is expressed by the cortex glia (Plazaola Sasieta et al, 2019) and possibly the SLC7 amino acid transporter Sobremesa (Sbm) (Galagovsky et al, 2018). Sbm is expressed in cortex glia and the subperineurial glia (see below).…”
Section: Cortex Gliamentioning
confidence: 99%